Generation Z purchase intentions: Does sponsorship disclosure matter? - Vesna Sesar; Anica Hunjet; Ivana Martinčević (Business Systems Research (BSR), 2023)
Background: Digital advertising and the amount of money spent on influencer marketing increases every year. Nowadays, it has become one of the most profitable ways to promote products and services and increase a company's profit through an endorsement on social media networks. Objectives: This paper explores the parallel mediating effect of brand awareness and influencer credibility between sponsorship disclosure and purchase intention among the Generation Z. Methods/Approach: We used a convenience sample method and used regression analysis to test the parallel mediator effect. Results: Findings of the research indicate that the direct influence of sponsorship disclosure on purchase intention is non-significant. However, this relation is significant when mediated by brand awareness and influencer credibility. Conclusions: The contribution of the research adds to the new knowledge in the field of influencer marketing and gives practical implications for brand managers who want to influence customers to buy.
Keywords: M1; M31; 330; influencer marketing; sponsorship disclosure; influencer credibility; brand awareness; purchase intention